How does Paul Ricoeur apply metapsychology to collective memory? - Lythgoe, Esteban (2018)
The concept of “abused collective memory” gathers two of Ricœur’s main lines of concern: history and psychoanalysis. The article aims to explain how this convergence was possible, especially, when the transposition of the Freudian metapsychology from the individual to the collective level was hindered by the Ricœurian emphasis on the Freudian libidinal economy. Our hypothesis is that this convergence required two intermediate steps. The first one gathered psychoanalysis and history within the larger framework of otherness as flesh. The second step was a transcendental turn, which would lead Ricœur to inquire about the structures of collective existence that make it possible to apply psychoanalytic categories at that level, rather than considering how this transposition can be done. By taking this turn Ricœur found that a phenomenology of the capable human being was the condition of possibility of a temporal ontology, and then, could describe this ontology as the condition of possibility of his phenomenology.